Letter to the Editor: Strengthening Antimicrobial Resistance Control Practice at Dr. M. Djamil Central General Hospital Padang, Indonesia - Djanas, Dovy (Rumah Sakit Umum Pusat (RSUP) Dr. M. Djamil, 2026)
Dr. M. Djamil Central General Hospital (RSUP Dr. M. Djamil) Padang has been at the forefront of efforts to combat antimicrobial resistance (AMR) through a comprehensive antimicrobial stewardship program guided by the Antimicrobial Resistance Control Committee (KPRA). The program focuses on three key components: surveillance, research, and education. Notable achievements include significant reductions in inappropriate antibiotic use, enhanced treatment strategies, and improved patient outcomes. A robust surveillance system has tracked both the quantity and quality of antibiotic use, leading to a marked increase in rational antibiotic prescriptions. Additionally, the implementation of antibiotic sensitivity patterns has allowed for more targeted therapies, particularly in treating multidrug-resistant organisms. Multidisciplinary collaboration through the Forum Kajian Kasus Infeksi Terintegrasi (FORKKIT) has further optimized patient care. Ongoing research into advanced diagnostic tools, such as RT-PCR, has advanced AMR control efforts, contributing to more precise treatments. Despite these successes, the continued prevalence of multidrug-resistant infections highlights the need for sustained efforts in surveillance, research, and education. Looking forward, RSUP Dr. M. Djamil Padang aims to reduce the incidence of these infections, improve prophylactic antibiotic administration, and align practices with national and international guidelines. The hospital’s commitment to advancing research and collaboration is vital in the global effort to preserve antibiotic effectiveness for future generations